Characteristics Differences Of Athlete Blood Pressure Of Sports Pre Nasional Sport Event In West Kalimantan - Isti Dwi Puspita Wati; Victor G. Simanjuntak (IKIP Budi Utomo Malang, 2020)
Blood pressure is an indicator of a person's health. Athletes should be have normal blood pressure levels. Exercise provides health benefits, one which is the prevention of hypertension. Exercise conditions and levels of physical and psychological stress put pressure on athletes so that is likely to affect blood pressure. High training intensity based on reviews has a positive impact on high blood pressure so that becomes normal. The purpose this study was to describe the characteristics of an athlete's blood pressure in anaerobic sports. The research method used research is survey research. This type of research is descriptive. The population in this study Pre-PON 2019 athletes in West Kalimantan, while the sample used was athletes in the anaerobic sports group. Anaerobic athletes are assumed to be a definite high-intensity exercise. The sampling technique in this study was purposive sampling. The results showed that from 10 anaerobic sports, 46 athletes were included in criteria for normal blood pressure, while 128 other athletes were included in criteria for prehypertension and hypertension. The conclusion of this study is athletes who experience prehypertension and hypertension will have an impact on health and will interfere with the athlete's performance.